2008
DOI: 10.1086/591528
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Outer Ejecta Knots in the Cassiopeia A Supernova Remnant

Abstract: Hubble Space Telescope images of the core-collapse supernova remnant Cassiopeia A are used to identify highvelocity knots of ejecta located outside the remnant's main emission shell of expanding debris. These ejecta fragments are found near or ahead of the remnant's forward shock front and mostly lie from 120 00 to 300 00 in radial distance from the remnant's center of expansion. Filter flux ratios when correlated with published spectra show that these knots can be divided into three emission classes: ( 1) kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 46 publications
4
81
1
1
Order By: Relevance
“…Moreover, follow-up optical studies suggested the highest velocity S-rich ejecta were, in fact, arranged in broad fans and not narrow jet-like streams as first thought (Hammell & Fesen 2008). Three-dimensional velocity reconstructions of the remnant's main shell and outlying optical ejecta have established that the NE and SW jet regions are on truly opposites sides of the remnant and conically distributed with opening half-angles of at least ∼ 40…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, follow-up optical studies suggested the highest velocity S-rich ejecta were, in fact, arranged in broad fans and not narrow jet-like streams as first thought (Hammell & Fesen 2008). Three-dimensional velocity reconstructions of the remnant's main shell and outlying optical ejecta have established that the NE and SW jet regions are on truly opposites sides of the remnant and conically distributed with opening half-angles of at least ∼ 40…”
Section: Introductionmentioning
confidence: 82%
“…The most complete previous survey of Cas A's outer ejecta knots was that of Hammell & Fesen (2008) A similar to the "fast-moving knots" (FMKs) commonly found in the main shell.…”
Section: The Population Of High-velocity S-rich Ejectamentioning
confidence: 99%
“…The jet and counterjet do not represent outflow in the classical sense. Instead they describe locations where the fastest-moving ejecta are observed well beyond the plateau and farthest from the explosion center (see, e.g., Hammell & Fesen 2008). To the southeast, iron-rich ejecta extend beyond the Bright Ring and into the plateau.…”
Section: General Background On Cas Amentioning
confidence: 99%
“…Located mostly between 120 " to 300 " from the center of expansion (Hammell & Fesen 2008), the distribution is aspherical showing jets of Si-rich and S-rich ejecta extending out to the largest distances in the northeast and southwest. The optical knots are rapidly expanding, ∼ 0.3 % yr −1 (an expansion parameter m ≈ 1), with proper motions of 1000s of km s −1 on the Bright Ring and up to 14,000 km s −1 for the optical ejecta at the tip of the jets (Fesen et al 2006b).…”
Section: Core-collapse X-ray Observationsmentioning
confidence: 99%